An Analysis upon India’s Trade and Trade Relationship with SAFTA Countries: Examining India's trade and trade relationship with SAFTA and its impact on regional economic cooperation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The South Asian Free Trade Area (SAFTA) is an agreement between the members of SAARC nations specifically India, Pakistan, Bangladesh, Bhutan, Sri Lanka, Afghanistan, Nepal and Maldives which was come to on 6 January 2004 at the twelfth SAARC summit in Islamabad. It made a free trade area of 1.8billion individuals in the region. The seven remote pastors of the region consented to a system arrangement on SAFTA to diminish traditions obligations of all traded merchandise to zero constantly 2016.However, SAFTA is an underlying advance in the development of the SAARC as a regional trade alliance and an economic association. There is much theory about its good impact on intraregional trade. As the greatest, and the most industrialized trading accomplice among the SAARC countries, India needs to take a lead in making the Regional Economic Cooperation a reality in South Asia. This investigation features India's trade and trade relationship with SAFTA everywhere and with every member of the trade coalition specifically. The investigation additionally features the macroeconomic diagram of the region refering to a few markers.